2021
DOI: 10.1111/psyp.13853
|View full text |Cite
|
Sign up to set email alerts
|

Learning to deal with delayed outcomes: EEG oscillatory and slow potentials during the prefeedback interval

Abstract: It is well established that the stimulus-preceding negativity (SPN) decreases in amplitude as a task is mastered, a phenomenon generally attributed to the reduction in anticipatory attention as feedback becomes less needed. Typically, the experiments supporting this assumption have used relatively short delays (<3 s). However, we found in a previous study that this decline in amplitude, although present during the 2.5-s prefeedback delay of a patterned key-pressing task, was absent with an 8-s delay. We reexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The half-sessions can be considered as two smaller sessions performed one immediately after another. Such treatment of half-sessions as consecutive measurements has been used in EEG analysis in various contexts [56][57][58][59]. Repeatability between such measurements can be considered as the minimum requirement, indicating that the frequencies of maximal coupling are stable at least at the time scale of the session, and could be meaningfully used to guide neuromodulation performed shortly after the EEG measurement.…”
Section: Reproducibility Between Measurements: Characteristics and St...mentioning
confidence: 99%
“…The half-sessions can be considered as two smaller sessions performed one immediately after another. Such treatment of half-sessions as consecutive measurements has been used in EEG analysis in various contexts [56][57][58][59]. Repeatability between such measurements can be considered as the minimum requirement, indicating that the frequencies of maximal coupling are stable at least at the time scale of the session, and could be meaningfully used to guide neuromodulation performed shortly after the EEG measurement.…”
Section: Reproducibility Between Measurements: Characteristics and St...mentioning
confidence: 99%
“…Because the SPN is produced by the anticipation of motivationally relevant stimuli, such as feedback on one's performance, it may be a useful tool in understanding feedback learning (Brunia et al, 2011), including credit assignment (Bhangal et al, 2021;Ren et al, 2017). A trait of the SPN that is particularly relevant to this thesis is that it has larger amplitudes if participants believe they have more control or involvement over their outcomes (Kotani et al, 2017;Masaki et al, 2010).…”
Section: The Stimulus-preceding Negativity (Spn)mentioning
confidence: 99%
“…Note. Time-frequency analysis example taken from Bhangal et al (2021). During the time when a subject was making a movement, alpha was suppressed (blue), followed by alpha activation (red) immediately after the cessation of the movement while the subject awaited feedback on their performance.…”
Section: Example Of Time-frequency Analysis Plotmentioning
confidence: 99%
“…Using the data from the published analysis (Bhangal et al, 2021), Figure 7 shows that there was no decline found in the P3 amplitude across either subblocks or tasks. We expected that aggregating trials with correct and incorrect responses would distort feedback-related components.…”
Section: Feedback-p3mentioning
confidence: 99%
“…The experiment summarized in Chapter 2 (Bhangal et al, 2021), attempted to determine whether subjects hold in mind a representation of a sequence of actions as they await feedback. If this representation is held in WM, its neural signature should diminish as the sequence is reduced toward a single chunk during automatization.…”
Section: Introductionmentioning
confidence: 99%